Knowledge, Attitudes, and Practices Toward COVID-19 Among the General Public in the Border Region of Jazan, Saudi Arabia: A Cross-Sectional Study - Almalki, Mohammed J. (Frontiers in Public Health, 2021)
Background The Saudi government had implemented unprecedented preventive measures to combat COVID-19, including intermittent curfews, bans on public gatherings, and launching awareness campaigns. This study aimed to assess the KAP toward COVID-19 among residents of the border region of Jazan, Saudi Arabia. Methods An online cross-sectional survey was distributed from May 4 to May 21, 2020, using a Google Form. The survey questionnaire covered demographic characteristics and KAP toward COVID-19. The KAP questions consisted of 17 items on knowledge, 4 items on attitude, and 6 items on practice. Results A total of 597 participants responded to the survey questionnaire. Overall, participants demonstrated a good knowledge of COVID-19, correctly answering 77% of the knowledge questions. Most of the participants exhibited good attitudes and acceptable practices toward COVID-19. Multiple regression analysis revealed that participants with a university education (B = 1.75) or post-graduate education (B = 2.24), those with an income >SR 10,000–20,000 (B = 1.38) or > SR 20,000 (B = 2.07), and those who had received a personal health education (B = 1.19) had higher COVID-19 knowledge scores (p < .05). The ordinal logistic regression analysis found that compared to being female, being male was significantly associated with worrying about COVID-19 (p = .024, OR = 1.78), willingness to receive a COVID-19 vaccine (p = .003, OR = 1.81), and willingness to report potential symptoms of COVID-19 (p = .046, OR = 2.28). Worrying about COVID-19 was significantly associated with pre-university education versus post-graduate education (p ≤.001, OR = 7.94) and university education versus post-graduate education (p ≤ .001, OR = 4.17). The binary logistic regression analysis found that compared to being female, being male was significantly associated with less face mask-wearing in public (p = .009, OR = .31): Females were 3.23 times more likely to wear a face mask than were males. Conclusions Most of the study participants had good knowledge, positive attitudes, and effective practices toward COVID-19. The findings of this study may help guide future awareness resources to the groups most in need in the Jazan region, particularly as the COVID-19 situation develops and changes.